2004
DOI: 10.1016/j.apsusc.2004.06.152
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of current transport in GaN and AlGaN Schottky diodes based on thin surface barrier model

Abstract: This paper attempts a rigorous computer simulation of the current transport in GaN and AlGaN Schottky diodes on the basis of the thin surface barrier (TSB) model recently proposed by the authors' group. First, a computer program was developed which can calculate current transport through an arbitrary potential profile of Schottky barrier by a combined mechanism of thermionic emission (TE), thermionic-field emission (TFE) and field emission (FE). Then, from the view point of the TSB model, attempts were made to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A previous study has reported that TFE is the dominant current transport mechanism for the recessed Al-GaN/GaN SBD. [9] Under the forward bias, the current due to TFE is given by [11,12]…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has reported that TFE is the dominant current transport mechanism for the recessed Al-GaN/GaN SBD. [9] Under the forward bias, the current due to TFE is given by [11,12]…”
Section: Resultsmentioning
confidence: 99%
“…A reasonable explanation is that tunneling occurs at a certain energy whose energy position is temperature dependent and this can be formulated by the Fermi-Dirac distribution functions. Then, the tunneling current by electrons from Ti to SiC can be calculated using the following equation [10]: where φ(z) the potential distribution, E z the normal component of the electron energy to the barrier, E p the parallel component of the electron energy, and f s and f m the Fermi-Dirac distribution functions for SiC and metal. A free electron model is used such as E z = ℏ 2 k z 2 /2m * , where k z is the wave number normal to the barrier.…”
Section: Resultsmentioning
confidence: 99%
“…This should produce a gradual dc current increase across the NW device as the magnitude of the negative bias increases. 21,22 The defect-assisted tunneling current is proportional to the integral of the tunneling probability, which is not thermally activated. 23 Consistent with this, the current-voltage characteristics for negative bias on the top Pt electrode do not show an exponential increase with applied voltage, unlike the positive bias case.…”
Section: Resultsmentioning
confidence: 99%